DESIGN OF AN AUTOMATIC PRECISION CONTROL DEVICE FOR SHAFT MACHINING (Conference Zone, 2022)
The shaft is shaped like a rotating body and serves to transmit torque. The design of the shafts can be compared to simple details, but the design of many shafts is complex